Mekanisme Coping Pada Remaja Dengan Perilaku Self-harm Berdasarkan Pendekatan Cognitive Behavior Therapy (CBT) - Nuril Azizah; Tristiadi Ardi Ardhani (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Adolescence is a critical period marked by physical, mental and emotional changes. Teenagers often experience social pressure at this stage, which can cause stress and difficulty controlling emotions. According to research, many teenagers engage in self-harm as a mechanism to cope with bad emotions and the inability to express them verbally. CBT has been proven to be a successful technique in helping adolescents recognize and change harmful thought patterns that trigger self- destructive behavior. Adolescents are taught to question negative beliefs and exchange them for more constructive beliefs through cognitive restructuring strategies. The findings of this study suggest that the use of CBT not only offers temporary improvements, but also gives adolescents the tools they need to deal with emotional difficulties in the future. Teens can improve their general mental health and lower their risk of self-harming behavior by learning healthier stress management techniques and the right support.